2015
DOI: 10.1111/jgh.12948
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2 polymorphism for development to hepatocellular carcinoma in East Asian alcoholic liver cirrhosis

Abstract: In alcoholic liver cirrhosis, investigations of ALDH2 polymorphism and ethanol consumption profile are useful for prediction of HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…It was suggested that metaregression was not always effective in explaining between-study heterogeneity [29]. In addition to metaregression, we conducted the Galbraith plot to explore heterogeneity, finding that the studies of Tomoda et al [19] and Abe et al [20] were the sources of heterogeneity for ALDH2 rs671. When these studies were omitted from the overall meta-analysis, the heterogeneity dropped down to 22.9% (P het = 0.247), without significantly affecting the pooled ORs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that metaregression was not always effective in explaining between-study heterogeneity [29]. In addition to metaregression, we conducted the Galbraith plot to explore heterogeneity, finding that the studies of Tomoda et al [19] and Abe et al [20] were the sources of heterogeneity for ALDH2 rs671. When these studies were omitted from the overall meta-analysis, the heterogeneity dropped down to 22.9% (P het = 0.247), without significantly affecting the pooled ORs.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis suggested a lack of association between ALDH2 rs671 and HCC susceptibility, but we could not exclude the possibility that an interaction between ALDH2 rs671 and alcohol drinking may have a role in the development of HCC. Abe et al found that the profile of alcohol consumption and ALDH2 rs671 had a close relation, and ALDH2 rs671 and the consumptive period affected HCC development in patients with alcoholic liver cirrhosis [20]. In addition, the study by Liu et al suggested that the association between ALDH2 rs671 and HCC might be significantly mediated by habitual alcohol consumption [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that most patients with a diagnosis of alcoholic LC were 40-49 years old, and four-fifths of the patients were diagnosed before they were 60 years old. This finding is probably due to the lower aldehyde dehydrogenase 2 activity, which is more susceptible to alcohol-induced liver injury in Asian and Chinese populations [20][21][22].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Accumulating evidence suggests that a drinking habit for an individual with the ALDH2*2 allele increases the risk of cancerous diseases, including upper aerodigestive, gastric, colorectal, hepatic, and lung cancer [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. For example, it was reported that individuals with the ALDH2*1/*2 genotype who were heavy drinkers (C46 g ethanol/day and C5 days/week) had a 38-fold greater risk of developing oesophageal cancer compared to non-drinking individuals with the ALDH2*1/*1 genotype, while drinkers with the ALDH2*1/*1 allele had only a 2-fold greater risk [47].…”
Section: Effect Of Aldh2*2 On Cancerous Diseasesmentioning
confidence: 99%